2006
DOI: 10.1089/cpb.2006.9.730
|View full text |Cite
|
Sign up to set email alerts
|

Personal Use of Work Computers: Distraction versus Destruction

Abstract: To explore definitions, frequencies, and motivation for personal use of work computers, we analyzed 329 employees' responses to an online survey, which asked participants to self-report frequencies for 41 computer behaviors at work. This sample (65% female, 74% European ethnicity, mean age of 36 years) was formed by soliciting participants through Internet Usenet groups, emails, and listservs. Results support a distinction between computer use that is counterproductive and that which is merely not productive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 11 publications
0
35
0
2
Order By: Relevance
“…Spector and Fox (2005) propose that personality factors (particularly those associated with emotional reactivity) play a role in acts of counterproductive behaviour. In line with this, it has been theorised that individual differences such as personality may play a key role in cyberloafing (Mastrangelo, Everton, & Jolton, 2006). Indeed, when controlling for age and gender, the Big 5 personality traits explain significant variance in cyberloafing, with less emotional stability, less conscientiousness, and greater extraversion associated with cyberloafing (Jia, Jia, & Karau, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Spector and Fox (2005) propose that personality factors (particularly those associated with emotional reactivity) play a role in acts of counterproductive behaviour. In line with this, it has been theorised that individual differences such as personality may play a key role in cyberloafing (Mastrangelo, Everton, & Jolton, 2006). Indeed, when controlling for age and gender, the Big 5 personality traits explain significant variance in cyberloafing, with less emotional stability, less conscientiousness, and greater extraversion associated with cyberloafing (Jia, Jia, & Karau, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Cyberloafing is the use of Internet and mobile technology during work hours for personal purposes (Bock & Ho, 2009;Johnson & Indvik, 2004;Lim, 2002;Mastrangelo, Everton, & Jolton, 2006). Cyberloafing has started to become a major problem for businesses.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study by Vitak et al (2011) has also revealed that cyberloafing frequency is greater among younger than older employees. The association between cyberloafing and age has been demonstrated by Ugrin and Pearson (2013) who studied North American employees and found that a greater number of older employees viewed social networking as abusive at work more than their younger counterparts, and hence younger individuals were more likely to misuse the Internet more seriously than the older individuals (Mastrangelo et al, 2006). The use of Internet was found to be more common among individuals aged between late 20s to early 30s (Reed et al, 2005).…”
Section: Age and Cyberloafingmentioning
confidence: 97%
“…The organization focused minor form of cyberloafing includes activities such as checking one's personal email and visiting mainstream news, while the serious form includes activities such as online gambling and downloading music (Blanchard and Henle, 2008). The taxonomy of cyberloafing by Mastrangelo et al (2006) divided this deviant behavior into nonproductive and counterproductive computer use. Nonproductive computer use refers to the use of computer at work for activities that are non-beneficial but nondestructive to the organization.…”
Section: Introductionmentioning
confidence: 99%